Nexus, Volume 6 essays in German Jewish Studies - Donahue, William Collins ca. 20./21. Jh; Helfer, Martha B. 1962- (Camden House, 2024)
Features a new section on the institutional settings of German Jewish Studies, a Film Forum on Shahar Rozen's 1998 documentary 'Liebe Perla', and interviews with Paul Mendes-Flohr and Barbara Honigmann, among other contributions